Familial Leiner’s disease with diminished fifth component of complement. - Inalöz, H.S.; Harman, M.; Akdeniz, S. (European Journal of Pediatric Dermatology, 2000)
Leiner’s disease is an uncommon childhood disorder that is characterized by severe seborrhea-like dermatitis usually with exfoliative erythroderma, severe diarrhea, failure to thrive, and recurrent gram negative and candidal infections. Familial involvement is less common and only two cases of this variant have been described to date. Familial Leiner’s disease has been suggested as a more dangerous variant with C5 deficiency in the patient’s serum and in failure to thrive and recurrent sepsis with an ominous prognosis. Combination therapy of systemic antibiotics and fresh frozen plasma would be life-saving in this disorder.